Penerapan Perawatan Luka Ulkus Diabetik dengan Nacl 0.9% pada Pasien Diabetes Melitus di RS PKU Muhammadiyah Karanganyar - Sepia Putri Regina Prayoga; Annisa Andriyani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Background : Diabetes Mellitus is a metabolic disorder caused by the pancreas being unable to produce insulin or unable to use insulin effectively, which is characterzed by an ncrease in blood sugar levels (Hyperglicemia), usually accompanied by the appearance of symptoms such as polyuria, polydipsia and polyphagia. The prevalence of diabetes mellitus n Marwah ward from April to June was 66 patients who experienced diabetic ulcers. Objective : to determine the level of Diabetes Mellitus wounds before and after treatment using 0.9% Nacl, and to see the comparison between the two. Method : This research shows that there is no change before and after wound treatment with 0.9% Nacl. On the degree of ulcuraton, but there was a reduction before treatment with Nacl 0.9% the wound appeared to have pus and was dirty and after treatment with Nacl 0.9% the wound looked clean and the pus was reduced. Results : This study showed that there was no change in the degree of ulceration, but there was a reduction in pus in the wound and the wound looked cleaner. Conclusion : After applying wound care with 0.9% Nacl to TN.